2000
DOI: 10.1242/jeb.203.17.2553
|View full text |Cite
|
Sign up to set email alerts
|

Early Thermal Experience has Different Effects on Growth and Muscle Fibre Recruitment in Spring- and Autumn-Running Atlantic Salmon Populations

Abstract: The consequence of early thermal experience for subsequent growth patterns was investigated in Atlantic salmon (Salmo salar L.). Spring- and autumn-running salmon were caught in upland (Baddoch) and lowland (Sheeoch) tributaries of the River Dee, Aberdeenshire, Scotland, respectively, on the final stages of their spawning migrations. The eggs were incubated at the simulated natural temperature regime of each stream, which was on average 2.8 degrees C lower for the Baddoch. The offspring, representing 11 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Ιn the Russian sturgeon Acipenser gueldenstaedtii (von Brandt & Ratzeburg 1833) the hatching rate was increased in correspondence to a temperature increase from 12 o C and 16 o C to 20 o C [ 84 ]. Generally, it has been observed that the variability in eggs incubation temperature even in low ranges can lead to substantial changes on the development of embryonic stages [ 85 87 ]. Hence, as proposed by Güralp et al [ 88 ], the development and timing of embryonic development and hatching apart from closely related to temperature, is species specific as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ιn the Russian sturgeon Acipenser gueldenstaedtii (von Brandt & Ratzeburg 1833) the hatching rate was increased in correspondence to a temperature increase from 12 o C and 16 o C to 20 o C [ 84 ]. Generally, it has been observed that the variability in eggs incubation temperature even in low ranges can lead to substantial changes on the development of embryonic stages [ 85 87 ]. Hence, as proposed by Güralp et al [ 88 ], the development and timing of embryonic development and hatching apart from closely related to temperature, is species specific as well.…”
Section: Discussionmentioning
confidence: 99%
“…While our analyses found no changes in nuclear recruitment to muscle bers, other studies examining temperate and cold-water teleost shes have seen an increase in myonuclear density with elevated temperatures. When Atlantic salmon, Salmo salar, eggs are reared at temperatures 3-4°C higher than their natal tributary thermal regime, fry exhibit higher nuclear densities and hypertrophic muscle growth shortly after hatching (Johnston et al 2000). Similarly, juvenile Atlantic herring (Clupea harengus), juvenile pacu (Piaractus mesopotamicus), and larval European sea bass (Dicentrarchus labrax) reared under elevated temperatures exhibit higher myonuclear densities, as well as increased hypertrophic and hyperplastic growth rates (Johnston et al 1998b ).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonid embryos incubate within freshwater sediments, often over winter, and can be subjected to highly variable and potentially harmful conditions within the lake or stream bed ( e.g ., Lavery & Cunjak, 2019). As a result, they may suffer sublethal damage that can affect their fitness in later life stages ( e.g ., Johnston et al ., 2000; Nislow et al ., 2004). For threatened and/or economically valuable species like Atlantic salmon ( Salmo salar ), embryo deformities have particular conservation relevance: deformities in live embryos have been linked to decreased survival later on (suggested by e.g ., Leatherland, 1993, Arias et al ., 1998, Einum et al ., 2002, Eriksen et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they may suffer sublethal damage that can affect their fitness in later life stages (e.g., Johnston et al, 2000;Nislow et al, 2004).…”
Section: Introductionmentioning
confidence: 99%